2016
DOI: 10.1111/famp.12234
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Couple Therapy on Service Utilization among Military Veterans: The Moderating Roles of Pretreatment Service Utilization and Premature Termination

Abstract: Couple therapy reduces relational and individual distress and may affect utilization of other health services, particularly among higher service utilizers. Although average decreases in service utilization are predicted among recipients of couple therapy, low utilizers of services may appropriately increase use. The relationship between couple therapy and service utilization was examined among a sample of 179 U.S. military veterans who received treatment in Veterans Affairs (VA) specialty couple therapy clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Currently, there are no reliable economic estimates associated with reductions in relationship distress beyond improvements in physical health or depression or reductions in service utilization. While these estimates are starting to emerge (e.g., Law & Crane, ; Madsen et al., ), the existing estimates were considered too preliminary to provide an accurate and comprehensive cost‐effectiveness analysis of each intervention compared to no treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are no reliable economic estimates associated with reductions in relationship distress beyond improvements in physical health or depression or reductions in service utilization. While these estimates are starting to emerge (e.g., Law & Crane, ; Madsen et al., ), the existing estimates were considered too preliminary to provide an accurate and comprehensive cost‐effectiveness analysis of each intervention compared to no treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study of cognitive, behavioral, and emotionally‐focused couple therapy interventions in VAMCs found that improvements in relationship satisfaction yielded important mental and physical health benefits such as decreased substance use and fewer depressive symptoms (Doss et al., ). As a result, those who were moderate or heavy users of mental health or physical health services before couple therapy saw significant reductions in frequency of these visits, thereby reducing healthcare costs (Madsen, Tomfohr‐Madsen, & Doss, ).…”
Section: Cost‐effectivenessmentioning
confidence: 99%
“…Indeed, an important measure of successful couple and family therapy can be attributed to therapists’ skills in engaging and retaining their clients (Robbins et al, 2003), with retention in treatment consistently related to successful treatment outcomes (Robbins et al, 2006). For example, one study of couple therapy found that those couples who stayed in therapy and did not drop out prematurely experienced a significantly greater decrease in healthcare utilization than those couples who dropped out prematurely, suggesting greater benefits from continuing in therapy (Madsen et al, 2017).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…A final consideration is that these findings are building on an accumulating literature showing that couples interventions are cost-effective and have associated secondary gains. Previous studies have shown that mental health and medical service utilization decrease following couple therapy, particularly in high utilizers [66][67][68]. Additionally, in the case of family therapy, secondary declines in service utilization have been observed even in individuals who did not participate directly in therapy [69].…”
Section: Implications and Future Directionsmentioning
confidence: 99%